2016
DOI: 10.1111/iji.12294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological relevance of antibodies in solid organ transplantation

Abstract: The two important issues affecting recipients of solid organ transplants and of importance to immunologists are (i) sensitization of the recipient to HLA antigens and the resultant humoral immune response leading to the development of anti-HLA antibodies; and ii) development of robust assays for early detection of humoral rejection post-transplant. Evidence from several studies clearly indicates that presence of circulating anti-HLA antibodies especially donor specific leads to early graft loss and high titres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 158 publications
0
24
0
4
Order By: Relevance
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor‐specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020; Foroutan et al., 2019; Mohan et al., 2012). This may lead to antibody‐mediated rejection and subsequently impair long‐term allograft survival (Mehra & Baranwal, 2016; Slavcev, 2013). However, there are special immunological aspects to consider among the elderly—both in transplant recipients and donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor‐specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020; Foroutan et al., 2019; Mohan et al., 2012). This may lead to antibody‐mediated rejection and subsequently impair long‐term allograft survival (Mehra & Baranwal, 2016; Slavcev, 2013). However, there are special immunological aspects to consider among the elderly—both in transplant recipients and donors.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor-specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020;Foroutan et al, 2019;Mohan et al, 2012). This may lead to antibody-mediated rejection and subsequently impair long-term allograft survival (Mehra & Baranwal, 2016;Slavcev, 2013 (Aw, Silva, & Palmer, 2007;Heinbokel et al, 2013). In consequence, elderly kidney transplant recipients have been shown to experience less acute rejection episodes than younger recipients (Noble, Jouve, Malvezzi, Susal, & Rostaing, 2019;Rana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While the importance of HLA matching has been postulated to be less important in the current era of more powerful immunosuppression, it has emerged again more recently as a potentially important factor influencing long‐term graft survival . Poor HLA matching is associated with the development of DSA and can lead to chronic antibody‐mediated rejection, the main cause of long‐term graft loss . A number of recent adult studies have demonstrated decreased graft survival associated with poor HLA matching .…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐HLA antibodies, particularly those directed against donor‐specific antigens, irrespective of whether appearing at pretransplant stage or develop de novo following transplantation are associated with adverse renal allograft outcome 1‐7 . However, not all DSAs are deleterious to the allograft.…”
Section: Introductionmentioning
confidence: 99%